Legal Discovery of Religious Court Judges in Marriage Itsbat Cases: An Effort to Reform Marriage Law in Indonesia - Husain, Husain; Abdulah Pakarti, Muhammad Husni; Kadir, Taqyuddin; Noor, Tajuddin; Saputra, Edy (Hukum Keluarga Islam IAIN LANGSA, 2024)
Marriage as the foundation of the family has an important position in society, but problems often arise regarding marital status, especially in itsbat of marriage cases. This study aims to identify and analyze the legal findings of Bandung Religious Court judges in itsbat of marriage cases, as well as the extent to which these legal findings contribute to the reform of marriage law in Indonesia. This research uses normative legal research methods with a statute and case approach. Primary and secondary data obtained from itsbat of marriage decisions, books, and journals that have the same discussion as this research. The results showed that the Religious Court judge in deciding the itsbat of marriage case had made various efforts to provide fairer legal protection for the parties who filed the application. The resulting legal findings, such as the application of the precautionary principle in assessing evidence, considering aspects of material justice, and providing innovative solutions in complex cases, have contributed significantly to the development of marriage law in Indonesia. However, there are still some challenges that need to be overcome, such as limited access to evidence and legal uncertainty in some aspects. Therefore, further efforts need to be made to improve the regulations and mechanisms for resolving itsbat of marriage cases, so as to provide legal certainty and justice for all interested parties.